Folklig dialektlexikografi 1991–2011 - Thelin, Eva (Nordiske Studier i Leksikografi, 2012)
This article investigates Swedish dialect dictionaries published from 1991 to 2011. Generally, these dictionaries have been compiled by lay lexicographers and show the vocabulary of a dialect spoken in one or a few adjacent parishes. Right from the start in the 18th century, the main purpose of publishing dialect dictionaries has been to document dialects and preserve them for posterity. As a consequence, the dialects were always presented as the source language. In 1991, however, a dictionary emerged using standard Swedish as the source language, thereby focusing on the needs of users who wanted to learn the dialect. Twenty years afterwards it can be determined whether this dictionary was an isolated phenomenon or if other similar publications have followed. Out of 115 dictionaries, I have identified 19 which in my opinion tend to learners’ needs in various ways. Quite a few of them treat dialects that are incomprehensible from a standard Swedish perspective. Another apparent change taking place during this period is the development of web-based dictionaries. I have been able to trace 59 presenting Swedish dialects. They differ from print publications in several ways. Two of the most obvious differences, concerning the number of words and the use of illustrations, are addressed and discussed. Somewhat surprising is the discovery that web publishers rarely invite interactivity. Nor do they provide for performing various types of searches or listening to sound samples.